Answer: y=-.667x+1
Explanation:
1. Firstly, substitute the coordinates of the two points into the slope intercept equation:
(1) y₁ = mx₁ + b
(2) y₂ = mx₂ + b
2. Then, subtract the first equation from the second:
y₂ - y₁ = m(x₂ - x₁)
3. Finally, divide both sides of the equation by (x₂ - x₁) to find the slope:
m = (y₂ - y₁)/(x₂ - x₁)
4. Once you have found the slope, you can substitute it into the first or second equation to find the y-intercept:
y₁ = x₁(y₂ - y₁)/(x₂ - x₁) + b
b = y₁ - x₁(y₂ - y₁)/(x₂ - x₁)